2010
DOI: 10.5032/jae.2010.03044
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Competency–based Extension Education Curriculum: A Delphi Study

Abstract: The purpose of this study was to determine the competencies entry–level Extension professionals will need in 2015. A Delphi panel of nationally recognized Cooperative Extension experts was developed to collect data. The 12 panelists reached consensus on 19 competencies. There were two key groupings among the competencies: extension program development process and core interpersonal skills. Cooperative Extension should examine ways to align its efforts with the competencies identified from this study in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 10 publications
(24 reference statements)
1
47
0
Order By: Relevance
“…This technique, first reported in 1963, has been employed for over half a century to gain consensus in multiple situations, ranging from views on transformative drugs developed by the pharmaceutical industry to forecasting population migration . Likewise, the Delphi approach has been used to assist in the planning of education, including the dermatological content of the undergraduate medical curriculum . More recently, Delphi has been utilized to prioritize research in various medical specialties, including occupational medicine, respiratory medicine and mental health …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique, first reported in 1963, has been employed for over half a century to gain consensus in multiple situations, ranging from views on transformative drugs developed by the pharmaceutical industry to forecasting population migration . Likewise, the Delphi approach has been used to assist in the planning of education, including the dermatological content of the undergraduate medical curriculum . More recently, Delphi has been utilized to prioritize research in various medical specialties, including occupational medicine, respiratory medicine and mental health …”
mentioning
confidence: 99%
“…[15][16][17] Likewise, the Delphi approach has been used to assist in the planning of education, including the dermatological content of the undergraduate medical curriculum. [18][19][20] More recently, Delphi has been utilized to prioritize research in various medical specialties, including occupational medicine, respiratory medicine and mental health. [21][22][23] In the current study, members of UK TREND conducted an electronic Delphi (e-Delphi) exercise to help prioritize translational research in dermatology.…”
mentioning
confidence: 99%
“…Competencybased professional development initiatives may promote job satisfaction and the improvement of core skills necessary for successful Extension work (Brodeur, Higgins, Galindo-Gonzalez, Craig, & Haile, 2011). Harder, Place, and Scheer (2010) asserted that by improving organizational…”
Section: Introductionmentioning
confidence: 99%
“…Leadership competency models provide a framework to guide leadership training for individual, interpersonal, and team development (Hollenback, McCall, & Silzer, 2006). Benge, Harder, andCarter (2011) andHarder et al (2010) found interpersonal leadership competencies such as communication and interpersonal skills were important competencies needed by pre-entry and early-career Extension agents in every program area. Specific to 4-H, competencies such as conflict management, communication, and multi-tasking were described as important by experienced agents (Harder & Dooley, 2007).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%